A Contagion through exposure to foreign banks during the global financial crisis. (Metro Manila, Philippines Asian Development Bank, 2017)
This paper develops an empirical methodology to test the contagion effect at the country level using bilateral data on bank claims between countries.
Keywords: Finance -- Government policy -- Asia; Financial institutions -- Developing countries; Electronic books